PENGARUH SISTEM PEMBELAJARAN FULL DAY SCHOOL TERHADAP HASIL BELAJAR SISWA KELAS XI IPS PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 12 PEKANBARU - Sari, Eka Permata; Suarman, Suarman; RM Riadi, RM Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The study aims to determine the influence of the full day school learning system on the learning outcomes of XI-grade students in economic subjects at Senior High School 12 Pekanbaru. The population in this study was all class XI students at 12 Pekanbaru State High School amounting to 168 students. This research uses simple random sampling technique which is the sampling of population members carried out randomly without regard to the strata in the population with the amount of 118 students being sampled. Data was collected using a questionnaire about the full day school that was distributed to respondents and requested a list of the grades of social science class XI economy class subjects for student learning outcomes. Data analysis uses simple linear regression test data analysis with a significant rate of 5%. Based on the results of full day school influence contributes to the student learning outcomes of 42.7% while the remainder of 57.3% is influenced by other factors that are not researched in this study.Key Words: Full Day School, Learning Outcomes